Omnichannel Communication Strategy in Branding Cosmetic Products in the Digital Era - Hazmy Fitriyasa; Achmad Jamil (Baca Dulu Publisher, 2024)
The Covid-19 pandemic has not stopped innovation in the cosmetics business in Indonesia. The cosmetics industry continues to grow, with cosmetics businesses even growing during the pandemic.consumer demand in 2021 has doubled. Social media plays a key role in influencing brand perception and image. Customers use this platform to search for product and company information, while companies communicate their brands and products to potential customers. Use of influencer marketingimpact on brand loyalty, especially in Generation Z and Millennials. Personal relationships built with influencers help in creating brand awareness and encourage product purchases. The concept of omnichannel, which combines communication through multiple channels, has become important in the beauty industry. This research uses theory social reference groups known as Herbert Hyman's reference group theory (1942). In this case the use of influencer Lesti Kejora who already has a fan group (fans) by MS Glow gave positive results to reach netizens. Lesti Kejora's attitude in choosing MS Glow products received various positives from Lesti fans These netizens use MS Glow products. For netizens who have used Previously, MS Glow was increasingly convinced that MS Glow was a new product and would continue to be used. The use of social media as a marketing channel can help increase the effectiveness of persuasive communication messages from MS Glow and effective communication with communication in physical stores.